Migration and Remittances in the Former Soviet Union Countries of Central Asia and the South Caucasus : What Are the Long-Term Macroeconomic Consequences? - Brownbridge, Martin; Canagarajah, Sudharshan (World Bank, Washington, DC, 2020)
Armenia, Georgia, the Kyrgyz Republic, and Tajikistan have all experienced substantial out-migration of workers and an associated inflow of workers' remittances over the past two decades. These four countries have much higher human capital, as measured by the Human Capital Index, than is typical for countries with similar levels of per capita income, and this may enable migrant workers to exploit opportunities to work in economies where labor productivity is higher. The inflow of workers' remittances has had effects analogous to those of Dutch disease in the Kyrgyz Republic and Tajikistan, which have experienced a large rise in expenditure to output and the share of services in gross domestic product, appreciation of the Balassa-Samuelson adjusted real exchange rates, and poor trade performance. In Armenia and Georgia, where remittances are a smaller share of gross domestic product, the effects were much more muted and their trade performance was much better.